Two new species of the genus Munnogonium (Isopoda: Asellota: Paramunnidae) from Argentina - Doti, Brenda L.; Roccatagliata, Daniel (Zootaxa, 2013)
Two new species of paramunnid isopods from Argentina are described: Munnogonium quequensis n. sp. from Buenos Aires Province (Quequén) and M. diplonychia n. sp. from Patagonia (Comodoro Rivadavia, Rada Tilly and Puerto Deseado). Both species are distinguished from their congeners by having a tight tuft of setae on the frontal margin. These setae have been discovered after examining the specimens under scanning electron microscope; under dissecting microscope they look like a short blunt median projection. M. diplonychia n. sp. differs from M. quequensis n. sp. by having bifid claws on pereopods II–IV. Eighty of the 92 specimens of M. quequensis n. sp. examined were found attached to the sea star Astropecten brasiliensis, a fact that suggests an association between these two species.